ANALISIS PROGRAM STRATEGIS DALAM PENGELOLAAN LAHAN KRITIS DAS BILA (Analysis of Strategic Program of Critical Land Bila Watershed Management) - Nuddin, Andi (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2017)
The rehabilitation program of critical land had been done since 1985 until 2001, but Bila watershed condition did not get better, even the width of critical land and erotion got more increase. It was caused of some factors, those are unaccurateness of program and technological aplication. Analysis of this research was focused on unaccurateness of strategic program. It wos to analysis and to formulate (1) main strategic program, and (2) suppoort strategic program on planning, actuating, and controlling of critical land bila watershed management. Analysis of Interpretative Structural Modelling was applied on this research, and the result shown that main strategic program must be applicated with : (1) to equalize vision and mission on watershed management was carried out according to cross territory, (2) to organize planning pattern on integrated watershed, (3) to coorporate in fund of cross territory, and (4) to develop monitoring and evaluating function of cross territory. Were as support strategic program were (1) to form watershed management coordination organization, (2) to develop contolling function and low investment cross territory.